Evalution of binary simulated Kalman filter and its application on airport gate scheduling - Zarifah, Mohamad Nor (2016)
Airport gate allocation problem referred to the search for optimal assignment of flights to gates at an airport. Assignment of flight to gates becomes very complex nowadays, especially for a big size airport. SKF is an optimization that has been introduced recently. This algorithm is based on mechanism of Kalman Filter where every agent estimates the global minimum/maximum. SKF can only solve continuous numerical optimization problem. From this algorithm, enhancement and modification of SKF is introduced. Exploitation of the distance between an agent and the best agent let the SKF operates in binary search space. In this study, the airport gate allocation problem is solved using extended version of Simulated Kalman Filter algorithm called Binary Simulated Kalman Filter (BSKF).The main objective of this study is to minimize the total walking distance of passengers either from a gate to entrance/exit or gate to a gate. So, a small case study in an airport with 40 flights, 14 numbers of planes and 16 gates has been chosen and for evaluate BSKF, fix parameter of run, iteration and number of agents was set up.